Implementasi Metode Tikrar Pada Program Tahfidzul Quran - Nurzannah Nurzannah; Prili Estiawani (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study was to know about the application of the Tikrar method in the tahfidzul Qur'an program at the Tahfidz Ad-Deen Islamic Boarding School in Teluk Mega includes; planning, implementation, and evaluation. This study uses a qualitative method. Data was collected using observation, interviews, and tests. The results of this study concluded that before the Tikrar method was implemented, the first teacher made a plan. Lesson plans are made as teachers do in other schools. Unfortunately, the application of the Tikrar method in the tahfidzul Qur'an program at the Tahfidz Ad-Deen Islamic Boarding School in Teluk Mega has not been following what is previously plan. The implementation of the Tikrar Method in the Tahfidzul Qur'an Program at the Tahfidz Ad-Deen Islamic Boarding School in Teluk Mega was used in two ways, namely by memorizing it at home and memorizing it in front of a tahfidz teacher. Evaluation is use after students finish presenting their memorization to the tahfidz teacher.